Utilization of PhET Simulation to Improve Understanding of Electrical Concepts - Sahwa, Sahwa (Scientica Education Journal, 2025)
The understanding of the concept of electricity is a challenge in learning physics because of its abstract and complex nature, various studies show that misconceptions often occur in students in understanding the relationship between current, voltage, and resistance, this study aims to analyze the effectiveness of Physics Education Technology (PhET) simulations in improving the understanding of electrical concepts, compare them with hands-on approaches, identify conceptual aspects that are experienced, as well as compiling evidence-based pedagogical recommendations, the method used is Systematic Literature Review (SLR) for 25 articles in the 2020–2025 range. The studies analyzed included various integrative approaches, such as blended learning, discovery learning, to project-based approaches, the results of the analysis showed that the PhET simulation consistently provided a significant improvement in the understanding of electrical concepts, with an average score increase of 15–30%, this simulation also encouraged learning motivation and active student engagement, compared to hands-on practice, the PhET simulation has advantages in terms of time efficiency and accessibility, PhET is a very effective learning medium to improve the quality of electrical learning in an interactive, efficient, and concept-based manner, integrating this simulation in the physics curriculum and teacher training is a strategic step to overcome conceptual obstacles in electrical learning.